Field observation on the effect of low-sodium and high-potassium salt substitute on blood pressure in the rural community-based population in China - Zhang, Gao-hui; Ma, Ji-xiang; Guo, Xiao-lei; Dong, Jing; Chen, Xi; Zhang, Ji-yu; Su, Jun-ying; Tang, Jun-li; Xu, Ai-qiang (Zhōnghuá liúxíngbìng zázhì, 2011)
To investigate the effect of commercial low-sodium and high-potassium salt substitutes on blood pressure in the rural community-based population in China. We conducted a quasi-experiment on 411 adults, who were 30 to 60 years of age, in 2 rural communities from Laiwu city in Shandong province of China on data from blood pressure screening. The subjects were divided into 2 groups: high blood pressure (HBP) and non-HBP (NHBP). Both groups and their family members took a low-sodium and high-potassium salt substitute for 3 months to replace the normal salt in their bodies. Blood pressure (BP) and 24-hour urinary sodium and potassium were measured regularly in the 2 groups. There was a continuously decreasing trend for BP at the end of the first month. Three months later, the mean BP decreased by 7.4 mm Hg (1 mm Hg = 0.133 kPa, t = 10.096, P = 0.000) for SBP and 3.8 mm Hg (t = 8.017, P = 0.000) for DBP in the HBP group, when compared to a 1.2 mm Hg (t = 2.507, P = 0.007) decrease on SBP and 1.0 mm Hg (t = 2.987, P